2017
DOI: 10.1364/ao.56.000777
|View full text |Cite
|
Sign up to set email alerts
|

Glass processing with pulsed CO_2 laser radiation

Abstract: Recent results of processing fused silica using a high-power Q-switched CO2 laser source with a maximum output power of 200 W are presented. Compared to the processing with continuous wave laser radiation, the main advantage of pulsed laser radiation is the influence of the light-matter interaction with high laser peak power at small average laser power. An application for the approach presented in this paper is the flexible manufacturing and form correction of optics. This laser-based process is ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 10 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…For laser figuring, a lateral resolution <100 μm and a vertical resolution <5 nm should be achieved [10] . Several experimental researches have been done to study high precision laser ablation for shape correction by a CW CO 2 laser [11] , ultrashort pulse laser [12,13] , and pulse CO 2 laser [14] . So far, however, it is reported that only a pulse CO 2 laser can meet the high precision requirements of laser beam figuring.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For laser figuring, a lateral resolution <100 μm and a vertical resolution <5 nm should be achieved [10] . Several experimental researches have been done to study high precision laser ablation for shape correction by a CW CO 2 laser [11] , ultrashort pulse laser [12,13] , and pulse CO 2 laser [14] . So far, however, it is reported that only a pulse CO 2 laser can meet the high precision requirements of laser beam figuring.…”
mentioning
confidence: 99%
“…Therefore, single pulse ablation is sufficient to represent the process. The ablation depth can be controlled through laser pulse duration or incident energy [10,14] . The quality of the final corrected surface is determined by the superposition of single pulse ablation.…”
mentioning
confidence: 99%
“…Laser processing is an effective and attractive method for surface modification of various materials, including surface texturing of semiconductors [1,2], corrosion prevention in biocompatible metals [3,4], and surface polishing of optical glass [5,6]. Employing CO 2 laser melting in a non-evaporative regime has enabled us to obtain surfaces of optical glass with a roughness smaller than 0.1 nm at a rapid processing rate of up to 5 cm 2 /s [5].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, for fluctuation with a spatial wavelength larger than 100 µm, Weingarten et al [5,6] introduced the laser-beam figuring (LBF) process to correct errors in the shape of a polished surface of fused silica with a precise and selective material ablation using a pulsed CO 2 laser. In the LBF process, laser ablation is highly localized and the ablation depth is strongly related to the pulse duration, which allows for the elimination of a wide fluctuation (over 100 µm).…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 lasers are widely used for machining glass [6,7] and have previously been used for smoothing and polishing of silica [8,9]. These techniques were performed with CO 2 lasers operating with a wavelength of 10.6 µm.…”
mentioning
confidence: 99%